Organizational Pride from 2018 to 2024: What Have We Learned and Where is the Field Heading? - Juniar Alisa; Nadya Ayu Lestari; Indi Ramadhani (Ann Publisher, 2026)
Background. Organizational pride has emerged as a significant emotional construct in the study of the work environment, yet systematic mapping of its intellectual development remains limited. Aim. This study aims to present a comprehensive bibliometric analysis of research on organizational pride by identifying intellectual structure, geographical distribution, and thematic evolution over time. Methods. The bibliometric approach is applied to data from scientific databases, analyzed using thematic mapping, factor analysis, and co-occurrence analysis. Results. Knowledge production was concentrated mainly in European institutions, particularly in England and Spain, and gradually extended to Asia and North America. A significant thematic shift was identified, namely from a focus on individual employee behavior to integration with strategic issues such as corporate social responsibility. Organizational pride is confirmed as a driving theme with high relevance and development in the contemporary organizational behavior literature. Conclusions. Organizational pride not only functions as an individual emotional response but also as a multidimensional strategic construct influenced by organizational support, leadership, and social perception. Implementation. These findings provide a systematic foundation for researchers and practitioners to identify research gaps and guide future studies of organizational pride in a variety of cultural and industrial contexts.